A hydrological tipping point and onset of Neolithic wetland occupation in Pestenacker (Lech catchment, S Germany). (15th February 2022) - Köhler, Anne; Wanger-O'Neill, Anneli; Rabiger-Völlmer, Johannes; Herzig, Franz; Schneider, Birgit; Nebel, Steven; Werban, Ulrike; Pohle, Marco; Kreck, Manuel; Dietrich, Peter; Werther, Lukas; Gronenborn, Detlef; et al.
Abstract: The reconstruction and understanding of tipping points in environmental systems have become an important issue for the global geoscientific community. This study focuses on the reconstruction of the Holocene deposition history of the Loosbach valley at the Pestenacker site, a Late Neolithic wetland occupation in the northern Alpine forelands of Central Europe (South Germany). Since 2011, it has been part of the UNESCO World Heritage 'Prehistoric pile dwellings around the Alps'. This study aims to reconstruct a potential passing of a Middle Holocene hydrological tipping point in the Loosbach valley and its interrelation with the Late Neolithic onset of valley occupation at that time. In this context, we make use of chronostratigraphical data sets about the Holocene fluvial dynamics of Loosbach stream from available archaeological excavation reports and spatially enlarge the local model of Holocene stream evolution with high-resolution direct push cross-sections from the proximate fen stratigraphies. As a result, the onset of the Late Neolithic settlement phase corresponds with a local hydrological tipping point at the wetland site of Pestenacker. Increased cooling and climatic humidity led to stream incision into the valley floor that resulted in draining, a local decrease of the groundwater table and the end of fen formation. As an apparently contradictory result of this process, increased water availability and run-off correspond with increased edaphic aridity on the valley floor. The latter may have made it possible to settle the valley floor during the late Neolithic. Highlights: Direct push sensing shows tripartite lithostratigraphy near Pestenacker wetland site. Mid-Holocene cooling and increased humidity resulted in the onset of channel flow. Stream incision led to fen draining, groundwater lowering & enhanced edaphic aridity. Late-Neolithic wetland occupation of Pestenacker site as a possible consequence.